2005
DOI: 10.1002/jmri.20300
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted MRI of the lung with hyperpolarized helium‐3: A study of reproducibility

Abstract: Purpose:To determine the reproducibility of several parameters of the ADC measurement by calculating the scanto-scan intrasubject variability. Materials and Methods:Measurements were performed using a gradient-echo sequence with a bipolar gradient for diffusion weighting (b ϭ 3.89 sec/cm 2 ). Five patients with pulmonary emphysema, and six healthy-lung volunteers were included in the study. Images were acquired after inspiration of 3 He during a single inspiratory breath-hold. To assess the reproducibility, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
3
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 29 publications
4
77
3
3
Order By: Relevance
“…Specifically, the sensitivity of the mean ADC for detecting microstructural changes in the lungs of patients with emphysema (31,91), asymptomatic smokers (69,102), and aging never-smokers (95) has been shown in various studies. The ADC measures have been shown to be highly reproducible (103,104) and to be potentially more sensitive than HR CT using the RA950 index (relative area of lung voxels below -950 Hounsfield units (Hu) (105)) for early detection of emphysematous changes in asymptomatic smokers (69,102). Several groups have shown that ADC measures are reproducible within better than 5% on consecutive scans and for studies on consecutive days (91,103).…”
Section: Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the sensitivity of the mean ADC for detecting microstructural changes in the lungs of patients with emphysema (31,91), asymptomatic smokers (69,102), and aging never-smokers (95) has been shown in various studies. The ADC measures have been shown to be highly reproducible (103,104) and to be potentially more sensitive than HR CT using the RA950 index (relative area of lung voxels below -950 Hounsfield units (Hu) (105)) for early detection of emphysematous changes in asymptomatic smokers (69,102). Several groups have shown that ADC measures are reproducible within better than 5% on consecutive scans and for studies on consecutive days (91,103).…”
Section: Copdmentioning
confidence: 99%
“…Several groups have shown that ADC measures are reproducible within better than 5% on consecutive scans and for studies on consecutive days (91,103). Moreover, in subjects lying in the supine position, ADC values have been shown to increase from the anterior to posterior regions of the lungs due to expected gravitydependent changes in alveolar volume (103,104). This sensitivity of regional ADC maps to processes known to affect alveolar volume makes DW He-3 MRI a potential tool for planning surgical therapies for lung volume reduction (106), and for monitoring individual regional disease progression in response to drug therapies.…”
Section: Copdmentioning
confidence: 99%
“…Key words: MRI; parallel imaging; helium; lung; phased array coil Lung imaging using hyperpolarized 3 He has received increased attention in the last several years for studying lung diseases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). So far, functional imaging, e.g., the apparent diffusion coefficient (ADC) or methods to observe the microstructure of the lung (12,13), requires long breath holds (up to 30 sec), which are the main barrier to applying this technology to patients with severe lung disease. Improvements in array coil methodology are a promising approach for increasing signal-to-noise ratio (SNR) and allowing significant acceleration of the image-encoding process.…”
mentioning
confidence: 99%
“…The ratio of these polarization changes allow the spatial mapping of ADC, with higher values allocated to larger air spaces (such as trachea and large bronchi). (190) ADC is homogeneously distributed in normal subjects, and becomes progressively more heterogeneous with normal smokers to emphysema (191)(192)(193)(194). ADC has been shown to increase under the influence of aging (195,196), emphysema (194,197,198) and due to gravity dependent compression of the lung (199); Figure 11).…”
Section: Hyperpolarized Gas Imagingmentioning
confidence: 98%